Пошаговое объяснение:
Или выразим y:
2/11.
x+3/8x=1/4
х•(1 + 3/8) = 1/4
1 3/8•х = 1/4
х = 1/4 : 1 3/8
х = 1/4 : 11/8
х = (1•8)/(4•11)
х = 2/11
Проверка:
2/11 + 3/8•2/11 = 1/4
2/11 + 3/44 = 1/4
8/44 + 3/44 = 1/4
11/44 = 1/4
1/4 = 1/4 - верно.
Пошаговое объяснение:
Или выразим y:
2/11.
Пошаговое объяснение:
x+3/8x=1/4
х•(1 + 3/8) = 1/4
1 3/8•х = 1/4
х = 1/4 : 1 3/8
х = 1/4 : 11/8
х = (1•8)/(4•11)
х = 2/11
Проверка:
2/11 + 3/8•2/11 = 1/4
2/11 + 3/44 = 1/4
8/44 + 3/44 = 1/4
11/44 = 1/4
1/4 = 1/4 - верно.